Theoretical investigation on unsteady stagnation-point flow towards a stretching or shrinking sheet. - Lok , Yian Yian (Universiti Sains Malaysia, 2016)
A study of the problem of unsteady separated stagnation-point flow towards a stretching or shrinking sheet was presented. By using a similarity transformation, the partial differential equations were reduced to a system of ordinary differential equations which were then solved numerically using bvp4c Matlab program. This Matlab program was capable of finding multiple solutions for the flow reattachment and flow reverse cases. The streamlines of the separation flow were also presented for both cases, i.e. when the origins of the stagnation flow and the stretching/shrinking sheet were aligned and non-aligned, respectively. It was found that adequate suction is necessary for the solutions to exist for the shrinking sheet case. It was also found that the suction process delays the boundary layer separation.